Design, validation, and reliability of an observational instrument for ball possessions in rugby union - Villarejo, D.; Ortega, E.; Gómez, M.-A.; Palao, J.-M. (International Journal of Performance Analysis in Sport, 2014)
The purpose of this paper was to design and validate an observational instrument to analyse ball possessions in rugby union. The instrument design and validation was done in six stages. The first and second stages had the objective of designing the observational instrument, a category system. In the third and fourth stages, the content validity was established and calculated. In the fifth stage, the instrument's reliability was tested. In the sixth stage, the observers used and applied the designed instrument. The number of experts that participated in the present study was 56 coaches. The final instrument included 99 behaviours for observation. Sixty were related to the initial phase, 14 were related to the game phase, and 25 were related to the end phase. Since all variables had an Aiken's V greater than 0.85, they were pertinent. This instrument design is valid and reliable for describing ball possessions in rugby and also for differentiating winning and losing technical and tactical performances. It allows for the analysis of the performance of rugby teams from a technical and tactical perspective.